A Tear by Nicky Manuputty: a Review of Alto Saxophone Playing Techniques and the Meaning of the Work - Teddy Nicolas Silalahi; Junita Batubara (Grenek: Jurnal Seni Musik, 2023)
A TEAR is a work of Nicky Manupputty who is a Saxophonist. The uniqueness of this song is that Nicky Manuputty uses a distinctive and different tounging. He has his own characteristics in playing saxophone in this work, namely tounging techniques resembling 'del-del' and resembling 'ta-ya' tounging. Therefore, the author is interested in researching the work A TEAR. The author found the technique of combining 'del-del' and 'ta-ya' tounging. The technique is the "dah-ya" tounging technique. In the 'dah-ya' technique, the author finds a tounging sound that is almost the same as that used by Nicky Mannuputty. The method used is descriptive qualitative method, by collecting data through youtube (https://youtu.be/76KrrEAQUek ), observation, literature study, articles/journals and documentation. The meaning of A TEAR is an expression of sadness. The results of this study are: 1) Showing the work of A TEAR live. 2) Introducing the works of Indonesian composers. 3) Knowing the techniques used by Nicky in his work, and the meaning of the work A TEAR.